Rare case of hypodiagnostics of subungual melanoma complicated by paraungual panaritium - Neretin, Evgeny Yurievich (European Journal of Oncology and Environmental Health, 2018)
Subungual melanoma in coexistence with the purulent inflammatory process occurs rather rarely in clinical practice. In spite of its outer localization and accessibility of examination patients are diagnosed mainly with III-IV stages by primary care physicians. We report our experience with clinical status of a 56 year old man that was inaccurately diagnosed with paraungual panaritium that coexisted with the purulent inflammatory process that led to the wrong surgical treatment. The presented case report shows that the doctor may reach an accurate diagnosis earlier with the use of stepwise algorithmic methods for diagnosing malignancy. Reaching the right diagnosis can be achieved taking into consideration both clinical and dermatoscopic clues.